2012
DOI: 10.1371/journal.pone.0051049
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Birth Order and Birth Interval on the Phenotypic Expression of Autism Spectrum Disorder

Abstract: A rise in the prevalence of diagnosed cases of autism spectrum disorder (ASD) has been reported in several studies in recent years. While this rise in ASD prevalence is at least partially related to increased awareness and broadened diagnostic criteria, the role of environmental factors cannot be ruled out, especially considering that the cause of most cases of ASD remains unknown. The study of families with multiple affected children can provide clues about ASD etiology. While the majority of research on ASD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
(59 reference statements)
1
7
0
1
Order By: Relevance
“…Existing literature has explored a number of other demographic variables (the siblings being of the same or different sex, sibling age, and the age difference between the older sibling and the child with ID) as correlates of siblings’ behavioral and emotional adjustment (Cuskelly and Gunn 2006; Ivey and Barnard-Brak 2009; Martin and Horriat 2012; Burke et al 2012; Goudie et al 2013; Walton 2016). However, these factors did not emerge as significant predictors in the logistic regression models in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature has explored a number of other demographic variables (the siblings being of the same or different sex, sibling age, and the age difference between the older sibling and the child with ID) as correlates of siblings’ behavioral and emotional adjustment (Cuskelly and Gunn 2006; Ivey and Barnard-Brak 2009; Martin and Horriat 2012; Burke et al 2012; Goudie et al 2013; Walton 2016). However, these factors did not emerge as significant predictors in the logistic regression models in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than socio-economic variables might also affect siblings’ behavioral and emotional adjustment. These include: the age and sex of the sibling (Hastings 2003; Verté et al 2003; Cuskelly and Gunn 2006; Orsmond et al 2009; Petalas et al 2009; Walton 2016); the sex composition of sibling dyads (Cuskelly and Gunn 2006; Ivey and Barnard-Brak 2009); birth interval (Martin and Horriat 2012); the number of brothers and sisters in the household (Burke et al 2012; Goudie et al 2013; Walton 2016), and whether the family is a single parent/carer household (Deater-Deckard and Dunn 2002; Kelly et al 2009; McHale et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…124 Earlier birth order and greater parity appear to be conflicting risk factors, because first-born children in sibship sizes of two, and later-born children in families with larger sibship sizes, are more likely to have ASD. 100 In addition, some studies have indicated that ASD symptom severity may be related to birth order, although these studies did not agree on which place in the birth order was more associated with severe symptoms, 173,174 possibly because interpregnancy intervals may also be a factor. 174 Interpregnancy intervals of less than 18 months 141 or less than a year have also been associated with autism in the second-born child.…”
Section: Birth Characteristicsmentioning
confidence: 99%
“…Le fait d'être né plus tôt et une plus grande parité semblent constituer des facteurs de risque contradictoires, parce que les aînés des familles de deux enfants et les enfants nés plus tard dans des familles plus nombreuses sont plus susceptibles d'avoir le TSA 100 . Des études ont en outre indiqué qu'il peut y avoir un lien entre la gravité des symptômes du TSA et l'ordre de naissance, même si ces études ne s'entendaient pas sur un lien plus étroit entre l'ordre des naissances et la gravité des symptômes 173,174 , peut-être parce que les intervalles entre les grossesses peuvent aussi constituer un facteur 174 . On a aussi établi un lien entre un intervalle de moins de 28 mois 141 entre les grossesses ou de moins d'un an et l'autisme chez le deuxième enfant 175 .…”
Section: Ordre Et Espacement Des Naissancesunclassified